Biomarkers of oxidative stress in patients with acute coronary syndrome - Vavlukis, Marija; Kamceva Gordana; Kitanoski Darko; Kotlar, Irina; Zdravkovska, Maja; Georgievska-Ismail, Ljubica; Kedev, Sashko (My University, 2016)
Purpose: To evaluate comparatively association between biomarkers of oxidative stress(OS) in patients with acute vs chronic coronary artery disease, and in comparison with healthy volunteers. Methods :Cross-sectional observational study was performed in patients admitted because of coronary artery disease (CAD). Pts were evaluated for their demographics, risk factors and co-morbidities, lipoprotein profile, HgbA1C and markers of oxidative stress: malondialdehyde (MDA) and hydroperoxids (HP), and antioxidant enzymes: superoxide dizmutaza (SOD), CATALASE and glutathione peroxidase (GPS). Pts were divided in 2 groups: pts with acute coronary syndrome (ACS) and chronic coronary artery disease (HCAD), and then subdivided, ACS pts in: STEMI, NSTEMI and APNS, HCAD in: asymptomatic CAD, revascularized and post MI patients. Statistical analysis: descriptive, t-test, ANOVA, Kruskall-Wallis ANOVA, correlation. Significance was determined at level of 0.05.Results :300 pts. 194 males and 106 females at mean age of 62.9±11,2 y were analyzed. 187 were with ACS and 113 with HCAD. 62,3% of pts. had HTA, 42,7% HLP, 28,3% DM, 57% smokers, 8% had anemia. There was no significant difference in the risk profile between the two groups. Mean values of the markers of OS (Table 1). Statistically significant differences didn’t existed between ACS and HCAD groups but inside the groups(Table 1), in lipid profile and HgbA1C in ACAD pts compared to HCAD.ACAD pts had higher HgbA1C, total, LDL and ApoB, but lower HDL-C and ApoA1. Correlation was found for HgbA1C and MDA (r=-,154**, p=0,008); age and total HP (r=-,143*, p=0,013); ApoA1 and total HP (r=-,157*, p=0,035);Conclusion: Markers of oxidative stress were significantly higher, and antioxidative activity was lower compared to healthy volunteers, but between ACAD and HCAD group significant differences were found only for HP from pro-oxidative, and SOD from anti-oxidative markers. Inside the groups, revascularized HCAD pts were with the highest pro-oxidative and lowest anti-oxidative activity, while in ACAD group, different markers of OS were the most pathological in different ACAD groups
Keywords: biomarkers; oxidative stress; acute coronary syndrome